Light rail service vehicular and pedestrian safety. - United States. Federal Transit Administration; Transit Cooperative Research Program; National Research Council (U.S.). Transportation Research Board; Korve Engineering, Inc. ([Washington, D.C.] Transportation Research Board, National Research Council, 1999)
"This TCRP digest provides the results of TCRP Project A-13 "Light rail service : vehicular and pedestrian safety" conducted by Korve Engineering."
Caption title.
"Sponsored by the Federal Transit Administration."
July 1999.
Keywords: Street-railroads -- United States -- Safety measures; Local transit -- United States -- Safety measures; Transportation -- Research -- United States